2021
DOI: 10.1186/s12866-021-02253-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a bacterial strain Lactobacillus paracasei LP10266 recovered from an endocarditis patient in Shandong, China

Abstract: Background Lactobacilli are often recognized as beneficial partners in human microbial environments. However, lactobacilli also cause diseases in human, e.g. infective endocarditis (IE), septicaemia, rheumatic vascular disease, and dental caries. Therefore, the identification of potential pathogenic traits associated with lactobacilli will facilitate the prevention and treatment of the diseases caused by lactobacilli. Herein, we investigated the genomic traits and pathogenic potential of a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 53 publications
3
21
0
1
Order By: Relevance
“…The role of the biofilm formation capacity in virulence was confirmed by Tang et al [ 30 ]. They observed that L. paracasei LP10266, isolated from blood and marrow samples of a patient with endocarditis, did not induce platelet aggregation and induced complement activation.…”
Section: Virulence Characters and Proposed Pathogenesismentioning
confidence: 76%
See 4 more Smart Citations
“…The role of the biofilm formation capacity in virulence was confirmed by Tang et al [ 30 ]. They observed that L. paracasei LP10266, isolated from blood and marrow samples of a patient with endocarditis, did not induce platelet aggregation and induced complement activation.…”
Section: Virulence Characters and Proposed Pathogenesismentioning
confidence: 76%
“…To date lactobacilli involved in infections have been little characterized at genome level but from the studies reviewed here it emerged that the ability to behave as a pathogen is inherent to the strain or clone, besides depending on patient’s underlying conditions and risk factors. Studies on isolate characterization indicated the capacity to form biofilm as the most relevant virulence factor [ 30 , 62 ]. Strikingly, this trait varied between clones of the same probiotic L. rhamnosus GG, indicating that the genetic stability of probiotic strains must be checked to avoid use of variants with newly acquired hazardous traits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations